1972
DOI: 10.1161/01.res.31.5.779
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Adenosine in the Human Term Placenta: DETERMINATION OF ADENOSINE CONTENT AND PATHWAYS OF ADENOSINE METABOLISM

Abstract: Adenosine, inosine, and hypoxanthine were isolated from human term placentas by paper chromatography of the diaJyzates of aqueous placental homogenates and quantified by ultraviolet spectroscopy. Placentas obtained upon vaginal delivery contained 230 ± 18 nmoles adenosine/g tissue, 300 ± 29 nmoles inosine/g, and 250 ± 19 nmoles hypoxanthine/g. Three prelabor placentas obtained by cesarean section contained 44 =t 3 nmoles inosine/g and 277 ± 22 nmoles hypoxanthine/g, but adenosine was not detected in two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Although the present study confirmed the expression of all four enzyme activities in the embryo-decidual unit, a coordinate developmental regulation model was not confirmed for the following reasons: (1) lack of coordinate regulation of 5'-NT and ADA activity and transcript levels in the embryo-decidual unit (days 4-8) and antimesometrium (days 9-13); (2) existence of a reciprocal distribution of 5'-NT (primary decidua) and ADA (secondary decidua) across the antimesometrium; and (3) persistently low PNP and XO activities between day 5 and day 13. The especially weak XO activity determined in the embryo-decidual unit was in agreement with studies of human term placental tissue (Sim and Maguire, 1972;Vettenranta and Raivio, 1988), indicating that the net flux of uteroplacental AMP catabolism proceeds with hypoxanthine, rather than nonsalvageable purine bases (Witte et al, 1991), as the main end-product. It is thus concluded that a major function of the purine nucleotide degradative pathway in the antimesometrium is the spatiotemporal regulation of adenosine levels.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although the present study confirmed the expression of all four enzyme activities in the embryo-decidual unit, a coordinate developmental regulation model was not confirmed for the following reasons: (1) lack of coordinate regulation of 5'-NT and ADA activity and transcript levels in the embryo-decidual unit (days 4-8) and antimesometrium (days 9-13); (2) existence of a reciprocal distribution of 5'-NT (primary decidua) and ADA (secondary decidua) across the antimesometrium; and (3) persistently low PNP and XO activities between day 5 and day 13. The especially weak XO activity determined in the embryo-decidual unit was in agreement with studies of human term placental tissue (Sim and Maguire, 1972;Vettenranta and Raivio, 1988), indicating that the net flux of uteroplacental AMP catabolism proceeds with hypoxanthine, rather than nonsalvageable purine bases (Witte et al, 1991), as the main end-product. It is thus concluded that a major function of the purine nucleotide degradative pathway in the antimesometrium is the spatiotemporal regulation of adenosine levels.…”
Section: Discussionsupporting
confidence: 83%
“…Aliquots of crude extract containing 0.1 to 10 pg protein were diluted to a final volume of 0.2 ml in 10 mM HEPES buffer, pH 7.4, containing 1 mM MgC1, and 1 mM 2-mercaptoethanol. Assay conditions were adapted from published methods to permit detection of different enzymatic activities in the same tissue homogenate (Abd-Elfattah and Wechsler, 1987;Schutz et al, 1981;Sim and Maguire, 1972). A parallel aliquot was heated at 95°C for 1 min prior to addition of substrate to provide a reference for "zero" activity.…”
Section: Determination Of Enzymatic Activities In Tissue Extractsmentioning
confidence: 99%
“…Second, this nucleotidase system, especially 5'-N, may modulate the feto-placental-maternal vasoactivity. The presence of adenosine in the human placenta was reported by Sim and Maguire (22) and some others also suggested that adenosine might play a role in maintaining placental microcirculation (10). In the heart, it is well known that adenosine, a potent vasodilatory agent, acts as a mediator of metabolic regulation of the coronary circulation and functions as an agent that can rapidly adjust coronary flow to changing oxygen requirements of the heart (3).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding this phenomenon, it was reported that the adenosine concentration in the placental tissue increased a hundred times after the onset of labor compared to that in the prelabored placenta (22). This increased concentration of adenosine might act as a vasodilator on the placental vessels.…”
Section: Bmentioning
confidence: 97%
See 1 more Smart Citation